Endoscopic Reconstruction of an Oral Feeding Route Using a Rendezvous Approach - Campos,Sara Teles de (2022)
Abstract Background: The approach to esophageal obstruction or discontinuity remains challenging and often involves complex reconstructive surgeries. The rendezvous endoscopic technique might be interesting in cases of complete esophageal obstruction. Case Presentation: Herein we describe a successful case of endoscopic recanalization of the esophageal lumen in a patient with a long-standing esophageal discontinuity resulting from several surgeries and chemoradiation for a squamous cell carcinoma of the hypopharynx, ending in a major cervical amputation, construction of a neopharynx, and definitive surgical closure of the superior esophagus with a PEG placement. With a rendezvous technique (peroral and through the gastrostomy) and under radiographic guidance, puncture from the neopharynx into the distal esophagus was performed, followed by balloon dilation and covered metal stent placement in order to reconstruct a neoesophagus. Five weeks later, the stent was removed (using a stent-in-stent technique). No complications occurred. The patient has been able to eat soft food and is being kept under regular endoscopic surveillance to control/treat a luminal stenosis of the neoesophagus. Conclusions: This case report illustrates a successful endoscopic treatment of post-surgical complete esophageal obstruction. This approach should be considered in the therapeutic armamentarium of these difficult clinical settings.